LEGAL PROTECTION FOR CREDITORS THROUGH THE ACTIO PAULIANA INSTITUTION IN CONNECTION WITH BANKRUPT ASSETS - Danila Elfayet; Richard C. Adam (RADJA PUBLIKA, 2025)
Actio Pauliana is an important legal instrument in the bankruptcy system, aimed at protecting the interests of creditors from the actions of debtors with bad intentions, such as the transfer of assets conducted before a bankruptcy declaration is made. This instrument allows creditors to annul legal acts of the debtor that could harm their rights, with the main principle being good faith. This article aims to analyze the application of actio pauliana in Indonesian bankruptcy law, focusing on the protection given to creditors in dealing with harmful transfers of debtor assets. This research uses a normative juridical approach, analyzing the legal provisions in the Bankruptcy and Suspension of Debt Payment Obligation Law (UU Bankruptcy and PKPU) and its application in practice. The results of the research show that actio pauliana can be an effective tool in maintaining fairness and transparency in debt settlement; however, its application still requires improvements in terms of oversight and coordination between relevant parties such as commercial courts, curators, and creditors. The recommendation is to update the regulations related to actio pauliana to address new challenges in bankruptcy practice and ensure the continuation of legal protection for creditors.